2016
DOI: 10.1039/c6ra01677d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of over-discharge on the lifetime and performance of LiFePO4/graphite batteries

Abstract: In this study, the degradation of a LiFePO4/graphite battery under an over-discharge process and its effect on further cycling stability are investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…Serial resistance represents the ohmic losses related to the electronic conduction-including electrode particles, tabs, and current collectors-and the ionic conduction through the electrolyte [65]. RC networks represent interfaces that form inside the cells.…”
Section: Fitting Processmentioning
confidence: 99%
“…Serial resistance represents the ohmic losses related to the electronic conduction-including electrode particles, tabs, and current collectors-and the ionic conduction through the electrolyte [65]. RC networks represent interfaces that form inside the cells.…”
Section: Fitting Processmentioning
confidence: 99%
“…When the battery was overdischarged to 0 V, its thickness increased by 70%, and the direct current resistance increased by 250%. Zheng et al [12] reported that when a battery was overdischarged to a low voltage, the solid electrolyte interphase (SEI) membrane dissolved and cracked; consequently, H 2 , CH 4 , and C 2 H 6 gases are generated in batteries whose overdischarge cut-off voltage is 1 V. Juarez et al [13] discovered that the maximum surface temperature of a battery during overdischarge was highly dependent on the C-rate. The surface temperature of a battery overdischarged at 1 C reached 79 • C. Ouyang [14] reported that the temperature rise of batteries increased during overcharging/overdischarging.…”
Section: Introductionmentioning
confidence: 99%
“…So far, considerable studies have been done to examine the inuence of overcharge/over-discharge on LIBs including electrochemical performances and aging characteristics. [6][7][8][9][10][11][12][13][14][15] Yuan et al 6 investigated the safety behaviors of a 32 A h prismatic LIB under abusive charge conditions by monitoring the internal and external cell temperature variations, and the results showed that the internal resistance of the overcharged battery became 5-7 times than that of the 100% SOC battery. Xu et al 7 systematically studied the failure mechanism of LiFePO 4 LIBs during overcharge conditions from 5-20% overcharge.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the impedance of the anode was much smaller than that of the cathode, but it dominated the impedance increase when the cell was overdischarged, which indicated that the SEI (solid electrolyte interface) change on the anode surface was much larger than that on the cathode. Besides, to investigate the degradation of an LiFePO 4 /graphite battery under an over-discharge process and its effect on further cycling stability, Zheng et al 12 conducted a set of experiments. Their results revealed that batteries over-discharged to 0.5-0.0 V experienced serious irreversible capacity losses of 12.56-24.88%, i.e., a serious loss of active lithium and anode materials occurred during the over-discharge process.…”
Section: Introductionmentioning
confidence: 99%